2022
DOI: 10.1155/2022/6279498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diffusion-Thermo on MHD Flow of a Jeffrey Fluid Past an Exponentially Accelerated Vertical Plate with Chemical Reaction and Heat Generation

Abstract: In many flow phenomenons of fluid with medium molecular weight, the energy flux is effected due to the inhomogeneity of concentration of mass. This contribution of the concentration to the energy flux is considered as diffusion-thermo effect or Dufour effect. In this research article the diffusion-thermo effect is addressed for the magnetohydrodynamics (MHD) flow of Jeffrey’s fractional fluid past an exponentially accelerated vertical plate with generalized thermal and mass transports through a porous medium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nasir et al 5 deliberated MHD stagnation flow through a surface of shrinking/stretching. The impact of MHD flow in prevailing magnetic area was studied by Bayones et al 6 Some authors Yasmin et al, 7 Hussain et al, 8 Shafique et al, 9 Munivenkatappa et al, 10 Khan et al, 11 Khan et al, 12 Song et al, 13 and Das and Patgiri 14 studied on MHD flow in different aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Nasir et al 5 deliberated MHD stagnation flow through a surface of shrinking/stretching. The impact of MHD flow in prevailing magnetic area was studied by Bayones et al 6 Some authors Yasmin et al, 7 Hussain et al, 8 Shafique et al, 9 Munivenkatappa et al, 10 Khan et al, 11 Khan et al, 12 Song et al, 13 and Das and Patgiri 14 studied on MHD flow in different aspect.…”
Section: Introductionmentioning
confidence: 99%
“…M. Ramzan et al [10] discussed the MHD fluid flow with the inclusion of a melting heat transfer with nonlinear chemical reaction across a slim needle in a porous system. Sarojamma et al [11], Ly et al [12], Shafique et al [13] studied the impact of linear chemical reactions and authors like Sharma and Borgohain [14], Mythili and Sivaraj [15], Hosseinzadeh [16], Muthtamilselvan [17], Ramzan et al [18] considered the impact of nonlinear chemical reaction on different flow problems.…”
Section: Introductionmentioning
confidence: 99%
“…Retardation and relaxation times in the Jeffrey fluid model are important for denoting the viscoelastic properties of polymeric materials, as shown by Bajwa et al [7]. Shafique et al [8] reported that Jeffrey's fluid is utilized in order to develop a mathematical model of blood flow in small arteries. Peristalsis, a classification of biological fluid movement, also uses it [9,10].…”
Section: Introductionmentioning
confidence: 99%